Подборщики льна - Луценко Владимир Михайлович (Новое в механизации растениеводства, 1984)
Экземпляры: КХ (20060619) / Инвентарный номер: 0265407 / Сис.шифр: 40.728 / Авт.знак: Л 86 / ГРНТИ: 68 / ББК: 40.728.4